Planning Study of Fender Spacing at Semayang Port based on PIANC - Tarigan, Baginta Veron; Harahap, Rima Gusriana; Destyariani Liana Putri (Naval Architecture Department, Kalimantan Institut of Technology, 2023)
Fender is one of the facilities whose role is very important for a dock. With the availability of a fender that can help absorb the energy of the ship's collision with the dock and can reduce the risk of damage to the dock structure and the ship's body. In the case found at Semayang Port Balikpapan, the fender is damaged due to the difference in the dock level with the docked ship. The position of the ship at the highest tide exceeds the limit set on the fender so that there is a difference that makes the fender work not optimally. The purpose of this research is to plan a fender system that is integrated into the dock structure. The method in this research is the finite element method with data processing and collecting primary data by making direct field observations. While secondary data in the form of ship data, wind, currents, and tides are obtained through the BMKG website and related agencies. The selection of the fender system is based on the calculation of the ship's impact energy on the Semayang Balikpapan pier. So that the results of the calculation of impact energy on the Fender amounted to 1844 kNm and obtained the type of fender, namely SCN 800 at 22 m for each fender with many 8 fenders.